Structural effects of dimensional nano-fillers on the properties of Sapium sebiferum oil-based polyurethane matrix: Experiments and molecular dynamics simulation. (12th August 2020) - Xu, X.L.; Bo, G.X.; He, X.; Tian, X.K.; Yan, Y.J.
Abstract: A study is presented on the experimental methods to synthesize bio-based polymer nano-composites with unique hierarchical microstructures having enhanced thermal stability and the mechanical properties. The solution-processable polymer nano-composites were prepared from Sapium sebiferum oil (SSO) bio-based polyurethane (BPU) and nano-materials with varied dimensional morphologies, including two-dimensional (2D) nanoplates, one-dimensional (1D) tubular structures, and zero-dimensional (0D) particles. The structures and properties of the nano-materials and their BPU nano-composites were characterized. The results showed that the nano-materials were evenly dispersed in the BPU matrix, and the thermal stability and the mechanical properties of the synthetic nano-composites were noticeably improved. The effect was pronounced with 0D aminated silicon dioxide nano-particles (SiO2 ), and 1D carboxylic acid functionalized multi-walled carbon nanotubes (MWCNTs-COOH), suggesting that structural dimensions of nano-materials have a marked effect on advanced properties of nano-composites. Furthermore, the structural specificity of nano-materials on the improvement of the nano-composite properties was validated by molecular dynamic (MD) simulations. MD simulations provided insight into the molecular interaction between nano-materials and the BPU matrix. Graphical abstract: Novel Sapium sebiferum oil-based polyurethane (BPU) nano-composites which was doped with various dimensional nano-fillers were successfully prepared. The properties and interaction mechanism of BPU nano-composites were investigated via experimental characterization and molecular dynamic (MD) simulations to elucidate the relationship between the micro-structure and the macroscopic-properties. Image 1 Highlights: Novel  Sapium sebiferum  kernel oil (SSO)-based polyurethane (BPU) were prepared. Structural effects of dimensional nano-fillers on the properties of BPU were studied using experiments and MD simulation. BPU nano-composites with low-dimensional nano-materials display outstanding thermal stability and mechanical properties. MD simulation provide theoretical method and is acceptable for the exploration of practical situation.